Spectroscopy Analysis of Antimicrobial Compound in Centella Asiatica Extract - Nurhanini Nahlul Muna Yusof; Khairina Idris; Tg Ainul Farha Tg Abdul Rahman; Liyana Amalina Adnan; Nurdalila A’wani Abdul Aziz (USIM Press, 2024)
MJoSHT2020, Volume 7, Special Issue, eISSN: 2601-0003